Workers vs Machines: Ottoman Tunis between Industrialisation and Colonisation - Nora Lafi (Revue Internationale de Politique de Développement)
The Ottoman province of Tunis between the 1850s and its integration into the French colonial sphere in the 1880s, was marked by the emergence of new issues directly arising from an international configuration undergoing profound change. This chapter aims to analyse the relationship between economic development, geopolitics and local issues in the last decades during which the province belonged to the Empire. It will home in on an emblematic conflict, one related to the fate of workers and artisans in fez factories as they protested against what they saw as unfair competition imposed by the European powers, and against the industrialisation that followed the mechanisation of production. These new operating conditions, in a market subject to the growing dominance of foreign trade and to instability in local production, gave rise to many protests. This chapter endeavours to compare and contrast the different levels and scales of this sector, to explain the impact of a new global dimension on local balances and the vectors of a new form of foreign interference. These conflicts also involved different ways of negotiating the reformed relationship between the Ottoman Empire and its province of Tunis in the face of the threat of ever-increasing foreign domination and colonisation. Focusing on the voices of the most modest local players, who spoke out to condemn the deterioration of their living conditions, and on the local and international context, the chapter aims to reveal the dynamic interrelation between different levels and issues, and individual destinies and wider perspectives, at a time of great historical change.